Algorithm of Nursing Approach in the Prevention of Complications of Bronchial Asthma and Assessment of Its Effectiveness - Razikova Ilmira Sadullaevna; Alikulova Dildora Yakhshibaevna; Khasanova Dilfuza Abdukhamidovna (Genius Journals, 2023)
The purpose of the study. Assessment of the effectiveness of the nursing approach in bronchial asthma by training and self - monitoring of patients to develop the qualifications and medical level of nurses according to the nursing approach algorithm for patients with bronchial asthma.
Keywords: bronchial; nurses; effectiveness